2016
DOI: 10.1007/s11832-016-0723-y
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer and intra-observer reliability in the radiographic diagnosis of avascular necrosis of the femoral head following reconstructive hip surgery in children with cerebral palsy

Abstract: PurposeThe incidence of avascular necrosis (AVN) following reconstructive hip surgery in cerebral palsy (CP) ranges from 0 to 69 % in the current literature. The purpose of this study was to determine the inter- and intra-observer reliability of radiographically diagnosing AVN in children with CP after hip surgery.MethodsA retrospective review of 65 children with CP who had reconstructive hip surgery between 2009 and 2012 at BC Children’s Hospital was completed. Anterior–posterior and lateral radiographs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Normal plain radiographs and physical exams can be falsely reassuring and delay appropriate referral [ 11 , 26 ]. In this context, several studies have found suboptimal diagnostic accuracy, reproducibility, and reliability [ 13 , 14 , 25 , 27 , 28 , 29 ]. The aim of this paper is to specifically clarify the association and accuracy of ONFH diagnosis between orthopedic surgeons, radiologists, and pathologists, considering imaging modes, microscopic and macroscopic bone features, and disease staging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Normal plain radiographs and physical exams can be falsely reassuring and delay appropriate referral [ 11 , 26 ]. In this context, several studies have found suboptimal diagnostic accuracy, reproducibility, and reliability [ 13 , 14 , 25 , 27 , 28 , 29 ]. The aim of this paper is to specifically clarify the association and accuracy of ONFH diagnosis between orthopedic surgeons, radiologists, and pathologists, considering imaging modes, microscopic and macroscopic bone features, and disease staging.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one of the twenty-four diagnoses agreed (interobserver kappa reliability coefficient of 0.58; percentage agreement of 85.71%), expressing moderate agreement. Literature regarding ONFH interobserver reliability has focused mainly on imaging staging correlation, with average kappa values ranging from 0.39 to 0.56, thus evidencing a poor interobserver reliability, especially among the intermediate stages [ 25 , 29 , 34 , 35 ]. In the present work, interobserver diagnosis reproducibility did not show a statistically significant difference when considering the different Ficat and Arlet stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in range with the currently published data. [4][5][6][7][8]12 Thirty-three children developed unilateral AVN and 5 children developed bilateral AVN. All 38 hips that developed AVN had femoral procedures While more children with GMFCS level V required a hip containment procedure, the rate of AVN development was similar for GMFCS levels III, IV, and V. While the unstandardized beta value was low, higher Reimers migration percentage was found to be a predictable risk factor in developing AVN, with children who developed AVN having a significantly greater (61.3 vs 51.1) Reimers migration percentage.…”
Section: Discussionmentioning
confidence: 99%